Oral Health Care Behavior in a Group of Turkish Children - (:unkn) unknown (IRANIAN SCIENTIFIC SOCIETY MEDICAL ENTOMOLOGY, 2009)
l Background: The purpose of this study was to evaluate oral health attitude and behavior of a group of Turkish children aged between 6-12 years Methods: A sample of 139 children attending Marmara University Dentistry School (MUDS) Department of Pediatrics Dentistry between December 2002 to April 2003 was selected. Results: The mean age for girls was 8.82 yr (SD=2.06) and for boys was 8.87 yr (SD=2.04). The reported age of starting tooth brushing was 4.5. 11.5% of children declared that they changed their brush once a year, 38.8% twice a year and 25.9% three times a year. 52.5% of children declared that they learned the principles of tooth brushing and the use of dental care products from the MUSD Department of Pediatrics Dentistry dentists during their visits and 78% of those children have applied what they teamed from them. Conclusion: It is found necessary to educate mothers of tooth brushing; since the children mostly receive their first training from their mothers. Besides, schools and kindergartens should provide oral hygiene instruction to parents and children.
Keywords: Oral health behavior; Turkish school children; Tooth brushing habits; DENTAL-CARIES; ATTITUDES; KNOWLEDGE; MOTHERS; CHINA; RISK